Tandem cyclization/arylation of diaryliodoniums via in situ constructed benzoxazole as a directing group for atom-economical transformation. Issue 4 (25th January 2022) - Peng, Hui; Liu, Qian; Sun, Yameng; Luo, Bingling; Yu, Tianyian; Huang, Peng; Zhu, Daqian; Wen, Shijun
Abstract : Linear diaryliodoniums often undergo only single arylation and leave equivalent aryl iodide as waste. Abstract : Linear diaryliodoniums often undergo only single arylation and leave equivalent aryl iodide as waste. Herein, we demonstrate that linear unsymmetrical diaryliodoniums could be tuned by a dual nickel/palladium metal system to accomplish one-pot cyclization/arylation. Of note, the in situ generated benzoxazole motifs could then be utilized as directing groups for subsequent C–H activated arylation from the often unwanted aryl iodide, exhibiting good reactions with atom economy and regioselectivity.